2006
DOI: 10.1002/dvdy.20874
|View full text |Cite
|
Sign up to set email alerts
|

Developmental cell death during Xenopus metamorphosis involves BID cleavage and caspase 2 and 8 activation

Abstract: Elimination of tadpole organs during Xenopus metamorphosis is largely achieved through apoptosis, and recent evidence suggest involvement of the mitochondrial death route and bax-initiated caspase-3 and -9 deployment. However, events upstream of the activation of Bax are unknown. In other models, proteins of the BH3-only group such as BID are known to assure this function. We show that Xenopus bid transcript levels increase at metamorphosis in larval cells destined to disappear. This increase correlates with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…Amphibian metamorphosis is a good model to understand the mechanisms regulating PCD [52][53][54]. The tail regression implicates an apoptotic pathway inducible by T3 hormone and involving some cell death executioners [55]. At the onset of metamorphosis, numerous apoptotic cells were observed in the spinal cord and caudal spinal ganglia [43,47,56], and a caspase-3 activity increased during climax in the spinal cord [48].…”
Section: Several Aspects Of Apoptosis At Metamorphosismentioning
confidence: 99%
“…Amphibian metamorphosis is a good model to understand the mechanisms regulating PCD [52][53][54]. The tail regression implicates an apoptotic pathway inducible by T3 hormone and involving some cell death executioners [55]. At the onset of metamorphosis, numerous apoptotic cells were observed in the spinal cord and caudal spinal ganglia [43,47,56], and a caspase-3 activity increased during climax in the spinal cord [48].…”
Section: Several Aspects Of Apoptosis At Metamorphosismentioning
confidence: 99%
“…Although cold-blooded animals like zebrafish and Xenopus are appropriate models in the study of apoptotic processes (Du Pasquier et al, 2006; Eimon and Ashkenazi 2010; Jette et al, 2008), little is known about the Bcl-2 family in non-mammalian vertebrates. Hsieh et al cloned the zebrafish ortholog of Bad and demonstrated that it is involved in apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Du Pasquier et al analyzed Bid expression in larval and adult tissues. In functional analogy to the mammalian protein, Bid was localized to the mitochondrion, inducing a drop of mitochondrial membrane potential (ΔΨm) (Du et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Proteins-Five members of the Xenopus Bcl-2 family of proteins (xBcl-w/xR1, xBcl-x L /xR11, xBax, xBid, and xBok) were functionally characterized in the previous studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In addition, partial or complete nucleotide sequences of 10 Bcl-2 family proteins (xBcl-2, xBcl-B, xBcl-G, xBcl2L12, xBcl2L13, xMcl-1, xBak, xBim, xBmf, and xNoxa) were deposited in the Xenopus nucleotide database, but the functions of their protein products remained uncharacterized (42)(43)(44).…”
Section: Identification and Rt-pcr Analysis Of Xenopus Bcl-2 Familymentioning
confidence: 99%
“…They are classified as either anti-apoptotic or pro-apoptotic, and the functional balance between these two groups controls the mitochondria-mediated intrinsic pathway of apoptosis. Although more than 10 members of the Bcl-2 family of proteins have been identified in Xenopus laevis (simply referred to as Xenopus hereafter), their functional characterizations are not yet complete (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%